1993
DOI: 10.1007/bf02928023
|View full text |Cite
|
Sign up to set email alerts
|

Plant regeneration through somatic embryogenesis in peanut (Arachis hypogaea L.)

Abstract: Somatic embryos were induced from immature cotyledons and immature embryonal axis of ,4rachis hypogaea L. on L-6 basal medium supplemented with NAA, picloram or 2,4-D at 5 -50 mg 1-1. Immature embryonal axis produced a higher number of somatic embryos in comparison with immature cotyledons. The highest number of responding cultures was produced on medium supplemented with NAA (50 mg l-l), while the highest average number of somatic embryos per culture was produced on medium with 2,4-D (10 or 20 nag 1-1) and pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The present studies have shown that it is possible to induce somatic embryogenesis and plant regeneration from immature cotyledon and immature embryonal axes of chickpea. Immature cotyledons (Lazzeri et al 1987, Ozias-Akins 1989, Eapen et al 1993, immature embryonal axes (Hazra et aL 1989) and immature embryos (Komatsuda andOhyama 1988, Kysely et al 1987) have been successfully used for somatic embryogenesis in other grain legumes as well.…”
Section: Discussionmentioning
confidence: 99%
“…The present studies have shown that it is possible to induce somatic embryogenesis and plant regeneration from immature cotyledon and immature embryonal axes of chickpea. Immature cotyledons (Lazzeri et al 1987, Ozias-Akins 1989, Eapen et al 1993, immature embryonal axes (Hazra et aL 1989) and immature embryos (Komatsuda andOhyama 1988, Kysely et al 1987) have been successfully used for somatic embryogenesis in other grain legumes as well.…”
Section: Discussionmentioning
confidence: 99%
“…Plant regeneration via somatic embryogenesis occurs in a wide number of plant species including some species of Arachis, such as A. hypogaea (Sellars et al 1990, Baker and Wetzstein 1992, Durham and Parrott 1992, Eapen et al 1993, Chengalrayan et al 1994, Joshi et al 2003, A. paraguariensis (Sellars et al 1990), A. pintoi (Rey et al 2000) and A. glabrata (Vidoz et al 2004).…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%